Guidelines for caring for HIV-infected adults and post-exposure prophylaxis of HIV infection - Snopková, Svatava; Rozsypal, Hanuš; Aster, Viktor; Sedláček, Dalibor; Kapla, Jaroslav; Jerhotová, Zdeňka; Olbrechtová, Lenka; Zjevíková, Alena; Dlouhý, Pavel; Jilich, David; Veselý, Dan (Klinicka mikrobiologie a infekcni lekarstvi, 2016)
Presented are general principles of care for HIV-infected persons following their admission to an AIDS care center, initiation of antiretroviral therapy and follow-up. Scientific research, drug development and new clinical data in recent years have led to a change in certain therapeutic perspectives and preferences for the treatment of HIV infection. Certain conditions are better specified, which affect the choice of antiretroviral regimens. Procedures and criteria for monitoring the effect of treatment and indication of post-exposure prophylaxis are specified. The development of this document was based on the latest updates of the most prominent international and European recommendations. It also reflects some of the new scientific information published in recent months. However, general recommendations cannot fully cover all the possible alternatives. They only state basic principles based on current clinical studies, clinical observation and practice. The present document should be the basic source of information for physicians involved in the treatment of patients with HIV infection and should provide a quick reference when selecting treatment regimens in terms of modern pharmacotherapy as well as information on the pitfalls of this treatment. Finally, it should be a support for negotiations between the professional society, state authorities and health care payers.This updated version of the guidelines follows the 2012 edition; once again, they are supplemented by a modified tabular overview.
Keywords: HIV infekce; hospitalizace; HIV Infections; Hospitalization; Post-Exposure Prophylaxis; Adult; dospělí; látky proti HIV; lidé; Anti-HIV Agents; Practice Guidelines as Topic; Humans; směrnice pro lékařskou praxi jako téma; postexpoziční profylaxe